Pengaruh profitabilitas dan ukuran perusahaan terhadap tax avoidance pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia - Prang, Bryan Bernard Herman; Warongan , Jessy D. L.; Mintalangi , Syermi S. E. (Yayasan Widyantara Nawasena Raharja, 2024)
Tax is the main indicator in the APBN because of the large percentage of tax revenue to maximize development in Indonesia. Taxes are obligations and burdens that reduce the firm’s net profit that is contrary to the firm’s goals. There are so many factors that influence tax avoidance, including profitability and firm size. The aim of this study is to determine the influence of profitability and firm size on tax avoidance in listed manufacturing firms on the Indonesia Stock Exchange. The sample in this study used a non-probability sampling method, namely a purposive sampling technique, thus obtaining a sample of 20 firms from a total of 175 firms. The analytical method used in this study is the multiple linear regression analysis method with data processing using IBM SPSS 26. The results of this study show that profitability has no effect on tax avoidance and firm size has a significant positive effect on tax avoidance.